Unravelling candidate genes associated with blast disease resistance in an elite green super rice varietal panel using genome-wide association study - Saxena, Harshita; Murugaiyan, Varunseelan; Ghimire, Bikash; Robiso, Christian John; De Asis, Erik Jon; Yanoria, Mary Jeanie; Raymer, Paul L.; Bahri, Bochra Amina; Ali, Jauhar (Wiley, 2025)
Rice blast disease, caused by the filamentous fungus Magnaporthe oryzae , significantly threatens global rice crops leading to yield losses worldwide. Given that existing resistance genes often fail to control rice blast due to the evolution of new virulent strains, identifying novel genes using modern breeding tools to enhance partial resistance is crucial for developing more durable and effective control measures. Here, we used a genome‐wide association study (GWAS) with 2698 high‐throughput single‐nucleotide polymorphism (SNP) markers to analyse 134 rice cultivars from the Green Super Rice breeding programme against two virulent rice blast isolates, M101‐1‐2‐9‐1 (M101) and M64‐1‐3‐9‐1 (M64). GWAS identified 12 potential quantitative trait loci (QTLs) for blast resistance: five against M101 on chromosomes 1, 2, 3, 4 and 7 and seven against M64 on chromosomes 1, 4, 5, 6 and 12, with no QTL in common against both. Notably, qM101_2 is within the 500 kb linkage disequilibrium (LD) block containing the known resistance gene Pib on chromosome 2, and qM64_12 . 1 and qM64_12 . 2 are within the Pi‐ta and Ptr gene cluster on chromosome 12. The remaining nine QTLs represented novel blast disease resistance sources. The identified candidate genes, including those encoding nucleotide‐binding site leucine‐rich repeats domains, protein kinases, resistance gene analogues and pathogenesis‐related proteins, may serve as a foundation for further studies to explore their potential role in enhancing disease resistance in rice.